2020
DOI: 10.18488/journal.8.2020.84.227.240
|View full text |Cite
|
Sign up to set email alerts
|

Crude Oil Price, Urbanization and Environmental Pollution in Nigeria: Evidence from ARDL Approach

Abstract: The impacts of crude oil price and urbanization on environmental pollution in Nigeria for the time frame of 1981 to 2016 is the main objective of this paper and the objective was achieved through the application of Augmented Dickey Fuller and Kwiatkowski Philip Schmidt Shin unit root tests together with Autoregressive Distributed Lag Model in the process of achieving stationarity and cointegration among the variables. The results obtained showed from ADF indicate that foreign direct investment and urbanization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Emissions were not influenced by long-term population expansion, and population growth could have an impact on CO 2 in the short term. When it came to environmental degradation in Nigeria, Maijama and Musa (2020) looked at how the country's urbanization and the country's crude oil price interacted using Kwiatkowski Philip Schmidt Shin and Augmented Dickey-Fuller tests in conjunction with the ARDL Model. Data from 1981 to 2016 was used in the study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Emissions were not influenced by long-term population expansion, and population growth could have an impact on CO 2 in the short term. When it came to environmental degradation in Nigeria, Maijama and Musa (2020) looked at how the country's urbanization and the country's crude oil price interacted using Kwiatkowski Philip Schmidt Shin and Augmented Dickey-Fuller tests in conjunction with the ARDL Model. Data from 1981 to 2016 was used in the study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A continuous unabated influx of people to urban centers with limited socioeconomic opportunities has led to a rise in unemployment, crimes, pollution, overcrowding, and acute housing problem with attendant pressure on limited and collapsing infrastructure (Aliyu & Amadu, 2017;Amao, 2012;Momoh et al, 2018;Oyeleye, 2013). In addition, high reliance on non-renewable energies for domestic and industrial use in Nigerian urban cities and towns has led to a significant increase in carbon dioxide emissions (Iroye, 2016;Maijama & Musa, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This cointegration lets us study how economic development and energy use affect the environment. [30]. Additionally, a large body of research has shown a positive link between energy use and CO2 emissions, meaning that higher energy use increases CO2 emissions [31,32].…”
Section: Energy Consumptionmentioning
confidence: 99%